2023
DOI: 10.1007/s11831-023-09949-2
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Approaches to Pedestrian Impact Simulation with Human Body Models: A Review

Abstract: The review paper discusses numerical human body models of pedestrians. The background of current trends in physical and mathematical pedestrian research is presented. Development, validation and areas of application of pedestrian body models are described. The differences between multibody models and finite element models are presented. Accident-based and experimental approaches to validation of the models are discussed. As a novelty, this paper presents an overview of multibody models used in forensic investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 137 publications
0
5
0
Order By: Relevance
“…Li et al [ 15 ] proposed a data-driven design method to optimize the engine hood through a machine learning model in order to achieve the lightweighting of the engine hood and to improve pedestrian safety. Mizuno et al [ 16 ] conducted a multi-body simulation analysis of different vehicle types and pedestrian body sizes and found that the decrease in pedestrian–vehicle re-contact was essential to reduce ground contact injury. The severity of pedestrian injury was not only related to vehicle speed but also to pedestrian sign, vehicle front parameter, and each participant motion involved in the collision [ 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [ 15 ] proposed a data-driven design method to optimize the engine hood through a machine learning model in order to achieve the lightweighting of the engine hood and to improve pedestrian safety. Mizuno et al [ 16 ] conducted a multi-body simulation analysis of different vehicle types and pedestrian body sizes and found that the decrease in pedestrian–vehicle re-contact was essential to reduce ground contact injury. The severity of pedestrian injury was not only related to vehicle speed but also to pedestrian sign, vehicle front parameter, and each participant motion involved in the collision [ 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The scene is recreated in the software using detailed scale sketches, with geometry, infrastructure elements, braking traces, collision point, and final position of the subjects after impact. The pedestrian model in PCCrash© uses a validated multibody (MB) system [20,21], which is based on anthropometric studies [22,23] that represent the male and female Spanish population. The parameters of the MB model of the pedestrian are adjusted (according to height, weight, age, and gender).…”
mentioning
confidence: 99%
“…We analyzed real accidents with pedestrian dummies with images captured with high-speed cameras and simulations performed in PC-Crash. PC-CRASH, multibody solvers, utilizes a contact algorithm similar to MADYMO, i.e., an algorithm based on the calculation of the depth of penetration [21].…”
mentioning
confidence: 99%
“…PC-CRASH, multibody solvers, utilizes a contact algorithm similar to MADYMO, i.e., an algorithm based on the calculation of the depth of penetration [21].…”
mentioning
confidence: 99%
See 1 more Smart Citation